Pengaruh Pembelajaran Pendidikan Agama Islam terhadap Perilaku Keagamaan Siswa - Afrianti Alyana; Murni Sukmawati; Rizqotussofia Rizqotussofia; Tuti Nuryati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic Religious Education not only serves as a means of conveying religious knowledge but also as a tool for character and moral development of students. Through a quantitative approach using survey methods, data were collected from a number of students as respondents. The analysis results show that there is a significant influence between the quality of PAI learning and the improvement of students' religious behaviour. The more structured and applicable the PAI learning received, the higher the level of appreciation and practice of religious values in the students' daily lives. The purpose of this research is to discuss the influence of PAI learning on students' religious behaviour. The type of this research is qualitative research using a literature review. Data sources are taken from books, articles, research results, news, websites, and other references related to the research. The data analysis technique uses content analysis where the researcher analyses content from various written sources. The results show that there are several influences of PAI learning on students' religious behaviour, namely, the role of Islamic Religious Education teachers, schools with madrasa curricula, lessons and activities with religious nuances, school culture and climate, social interactions, as well as facilities and resources.